Triple detection of tumor protein p63, Ki-67 and Alpha-methylacyl-CoA racemase in pathological diagnosis of prostate cancer: p63, Ki-67 and Alpha-methylacyl-CoA racemase in diagnosis of prostate cancer - Niu, Ming; Zhao, Danbo; He, Ruixue; Qin, Ling; Li, Zhikai; Zhang, Side; Chen, Lijun (Journal of Medical Biochemistry, 2025)
Objective: To explore the value and significance of triple immunohistochemical detection of Alpha-methylacyl-CoA racemase (AMACR), p63 and Ki-67 in the pathological diagnosis of prostate cancer.Methods: A total of 156 paraffin-archived prostate biopsy samples collected from our hospital from June 2023 to August 2024 were selected as research materials. The expression levels of AMACR, p63 and Ki-67 in puncture samples from 48 patients with prostate cancer, 32 patients with high-grade prostate intraepithelial neoplasia, 26 patients with low-grade prostate intraepithelial neoplasia and 50 patients with benign prostatic hyperplasia were detected via immunohistochemistry.Results: There were statistically significant differences in the positive expression rates of AMACR, p63 and Ki-67 among the different groups of samples. The positive expression rate of AMACR in the puncture samples of the prostate cancer group was 100%, among which the high expression rate was 81.25%. The negative expression rate of p63 was 97.92%, which was significantly greater than that of the other three groups. The positive expression rate of Ki-67 was 81.25%, and the high expression rate was 54.17%. AMACR is related to the long diameter of the tumor, TNM stage, degree of differentiation and Gleason score in patients with prostate cancer. The rates of high AMACR in patients with tumors with long diameters ≥1.5 cm, stage II–III, moderate to highly differentiated, and Gleason scores ranging from 8--10 were significantly higher than those in patients with tumors with long diameters
Keywords: Prostate tumor; Immunohistochemistry; Alpha-methylacyl-CoA racemase (AMACR); P63 protein; Ki-67 antigen